KETERAMPILAN MENGELOLA KELAS OLEH GURU PADA PEMBELAJARAN IPS DI KELAS VIII - Wendi Wendi; Okianna Okianna; Husni Syahrudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims at describing teachers’ classroom management skills in social science learning to year-8 A and year-8 B of SMP Negeri 23 Pontianak in regards to the way the teachers create the right learning atmosphere, set the classroom situation, and manage good interaction in teaching-learning process. This study uses descriptive qualitative approach. The data of this study is the teachers of social science and the students of year-8 A and year-8 B. The technique of data collecting is through observation, interview and documentation. The technique of data analysis is through reduction, display and deduction. The validity of the data is through triangulation of technique and source. The finding of the study shows that the teachers’ skills in classroom management in social science learning to year-8 A and year-8 B of SMP Negeri 23 Pontianak is relatively good from several ways; (1) applying the principles of classroom management including warmth, enthusiasm, challenge, variety, flexibility, emphasis on positive things and cultivation of discipline. (2) the setting of the classroom tends to only change the seat position when it is students’ group-work. (3) management of teaching-learning interaction is done through the skills of opening and closing, explaining, questioning, reinforcing and discussion guiding. Keywords: Classroom Management Skills, Social Science Learning, Teachers